Investigating experimental and environmental factors to provide a mechanistic understanding of benthic algal biomass accumulation in freshwater streams - Beck, Whitney S., author; Poff, N. LeRoy, advisor; Hall, Ed, committee member; Hoeting, Jennifer, committee member; Spaulding, Sarah, committee member (Colorado State University. Libraries, 2019)
To view the abstract, please see the full text of the document.
Keywords: freshwater; periphyton; nutrients; algae